Calcários albianos de campo petrolífero na Bacia de Campos: fácies, diagênese e modelo deposicional - Okubo, Juliana [UNESP] (2014)
Carbonate rocks from the Macaé Group (Albian), particularly the Quissamã Formation, are important reservoirs of the Campos Basin. A fundamental problem related to modelling of hydrocarbon reservoirs is the characterization of petrophysical heterogeneties, which is closely related to temporal and spatial variability of sedimentological properties (i.e., depositional model). Geological models previously presented for Macaé Group rocks show facies and their lateral variation. On the other hand, those models lack information about depositional processes of these facies. This work presents depositional model for Macaé Group carbonates including the upper part of the Quissamã Formation and the lower part of the Outeiro Formation. The studied interval comprises a 200-400m thick section within an oil field located in southwest portion of the Campos Basin. Facies and facies associations (FA) were defined by macroscopic analyses of rocks (320m cores), supported by microscopic analyses. Electrofacies were created by supervised and unsupervised approaches in 28 wells. Distinct sedimentary cycles with three diferent scales (high, medium, low) were interpreted based on the vertical facies sucession. Eleven sedimentary facies were recognized: A) oolitic grainstone, (B) oncolitic grainstone, (C) oncolitic peloidal grainstone, (D) oncolitic bioclastic packstone, (E) peloidal bioclastic packstone, (F) bioclastic packstone, (G) oolitic packstone/wackestone, (H) wackestone, (I) pithonellids wackestone, (J) bioclastic wackestone with glauconite e (K) dolomite. Facies A to H represent rocks of the Quissamã Formation whereas facies I and J represent rocks of the Outeiro Formation. Facies association A+B (FA1) is related to deposition in shallow depths, above the fair weather wave base (FWWB). Facies C and D (FA2) were formed in waters slightly weaker or more sporadic than FA1, close to the FWWB. Facies association E+H (FA3) is related to calm waters...